Metamorfoses na Região do Petróleo : a criação de territórios a partir da implantação da Petrobrás - Silva, Daniel Almeida da (2005)
Among academic and social groups the questions about territory has be coming each more effective. This reflects the interesting of society by the subject, as result the growing and competitive global integration of places and regions. By this way, this search try to revel the changes occurred at the oil region, which began since the implantation of PETROBRAS at 1963. The environmental approach made itself necessary because it is the stage for metamorphic actions. These metamorphic actions direct the social-economical questions, from witch one is done an investigation about demographics and life quality conditions, where by a side had an intense process oil extract extraction, immediately provoking a new direction to agriculture, giving space to. This way, the great soil quality and the clime with a regular at its irregularity, despite of the annual concentration, favorable to gender production, haven t became an important question at the regional economy. The region municipalities, at most, show an agricultural vocation to product sugar cane. Had a generalized grown of the income, the population past to receive better salaries, had also a considerable enlargement of services and IDHM. The royalties allowed advances on services of: energy, supply and treatment water and sanitation. The oil region, for this way, is indicated by PETROBRAS insertion as a builder and agent of new territories.